Therapy Lipbalm (AynaRosé.co) / Nur Aina Najwa Roslan - Nur Aina Najwa, Roslan (2020)
AynaRosé.co is a health and beauty company offering a therapy Lip Balm with healing properties that helps to rejuvenate and heal the lips giving it the perfect moisture it needs to prevent from cracking and drying. Our company targeted working people of both male and female in the age of 25 and above. We targeted them because when working,our lips are easily dehydrated,either working indoor or outdoor,the temperature will affect the lips and causes it to be dry and cracked. Our targeted location is in Kuala Lumpur because kuala lumpur is one of the busiest city and will always be fill with people and tourist. So,it will be easier to attract customers. AynaRosé.co product is 100% natural made with organic ingredient and had been tested 100% safe and no chemical. Our product can be used by everyone especially people with sensitive lips and it will not harm any type of lips. We also gave our customers chances to choose based on their preferences in the aspect of smell. Our company is also made by the office workers itself, we uses a very high tech machine and handle the manufacturing process ourself. We also choose the best quality ingredient to make the product to the finest quality we can have. Our company is still new in the industry and we are hoping to slowly rise as the best brand. Our company wants to achieved to be not only a quality brand but also a multimillion company so we are able to bring more quality product for people. Our sales forecast for this year is around Rm1,341.00, there are an up and down throughtout the monthly charts based from some facts. We have also set our sales forecast goal for the next three years. We will try to achieve our forecast goal as we had planned.